Cooperative Learning Model of Group Investigation Type on Students' Critical Thinking Skill and Scientific Communication Skills - Rosiani, Ema; Parmin, Parmin; Taufiq, Muhamad (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2020)
This research aims to find out the influence of the application of the group investigation cooperative learning model on critical thinking skills and the scientific communication skills of students. True Experimental Design in the form of Posttest-Only Control Design is a research design applied to this research. Analysis of the data obtained showed that the correlation coefficient value of the critical thinking skills test data was r = 0.672. The results of the t-test analysis showed that t-count = 5.671 and t-table = 2.042, which means that there is an influence on the application of the cooperative learning type group investigation model in the experimental class as seen from the coefficient of determination (KD) of 33%. The value of the correlation coefficient in the analysis of students' scientific communication skills data is r = 0.9. The value obtained from the calculation of the t-test is t = 3,576 and t table = 3,182 which means that there is an influence on students' scientific communication skills after the implementation of the cooperative learning model group investigation type. The coefficient of determination of students' scientific communication skills is 81%. The conclusion that can be drawn from the research that has been carried out is that there is an influence on the ability to think critically and the scientific communication skills of students after the implementation of the cooperative learning model group investigation type in the learning process.